Mountain Apiculture and Environmental Dynamics: Impact of Climate Variability on Bee Farming in OKU, CAMEROON. - Eric Kongnso MOYE; Jude KWEI; Ignatius Ngala KIMING (Indonesia Strategic Sustainability, 2020)
This study aims at analyzing the effects of climate variability on bee farming in Mount Oku. The guiding premise is that climate variability has brought about environmental changes causing a fall in the quantity and quality of honey. A mixed research approach was adopted in collecting data. Questionnaires were administered to 90 purposively selected bee farmers and interviews conducted with key actors in honey production. SPSS, version 20.0 was used to analyze data while the cumulative difference index helped establish climatic anomalies and trends. Findings revealed falling rainfall trends with marked seasonal variations. Temperatures show a rising trend with little but sensitive anomalies. This has affected periods of flowering for bee plants as acknowledged by 97% of bee farmers. Hive colonization rate has been decreasing (74% - 55%), with an increasing rate of abscond (34% -46%), resulting in a reduction in honey yields. Climate variability has increased the magnitude of other environmental stressors such as bush fires and forest degradation, while reducing the growing period of some bee plants. The coping strategies put in place by bee farmers are limited and policies need to address this situation so as to maintain the quality of OKU honey.